The fecal bacteria - Sadowsky,Michael ed; Whiteman,Richard L; Sadowsky, M. J.; Whitman, Richard Lincoln (Washington, DC : ASM Press, 2011)
"The Fecal Bacteria offers a balanced, integrated discussion of fecal bacteria and their presence and ecology in the intestinal tract of mammals, in the environment, and in the food supply. This new volume covers their use in examining and assessing water quality in order to offer protection from illnesses related to swimming in or ingesting contaminated water, in addition to discussing their use in engineering considerations of water quality, modeling, monitoring, and regulations. Fecal bacteria are additionally used as indicators of contamination of ready-to-eat foods and fresh produce. The intestinal environment, the microbial community structure of the gut microbiota, and the physiology and genomics of this broad group of microorganisms are explored in the book."--pub. desc.
Keywords: Enterobacteriaceae; Enterobacteriaceae; Environmental Monitoring; Feces; Fresh Water